E-Storybook Media with Problem-Based Learning Model Enhances Learning Outcomes on Human Respiratory Topic - Farah Fauzia Zahra; Barokah Isdaryanti (Postgraduate, University of Mataram, 2025)
This research aims to develop E-Storybook with Problem-Based Learning model that are feasible, effective and practical to improve students' learning outcomes on human respiratory topic. The study come under the Borg and Gall model of research and development (R&D). All of 24 students at SDN 3 Krasak participated in this study. Data were collected using test and non test technique. Data on the feasibility, effectiveness and practicality of learning tools were obtained from feasibility tests, N-gain tests and practicality tests. Feasibility data was obtained from the assessment of 2 validators consisting of media expert and material expert from Universitas Negeri Semarang. The results of feasibility validation conducted by media and material experts showed the average expert validation result of 92.5%, which falls into the feasible category. According to the t-test results, there is a significant difference between learning outcomes before and after media consumption. Furthermore, the N-gain test results indicated a high category, with a small-scale score of 73% and a large-scale score of 84%. These results support the conclusion that creating E-Storybook materials using the Problem Based Learning model is both practical and efficient for use in order to enhance grade V students' learning outcomes regarding human respiratory content.